2005
DOI: 10.2135/cropsci2005.0673
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Yield and Stand Characteristics of Switchgrass in South Central U.S. Environments

Abstract: Optimizing feedstock production from switchgrass (Panicum virgatum L.) requires careful matching of genotype to environment, especially for southern U.S. regions. Nine genotypes from four combinations of ecotype and morphological type were harvested once yearly in autumn for 3 or 4 yr at five locations across Texas, Arkansas, and Louisiana that varied in latitude and precipitation. Genotypes were evaluated for dry matter yield (DMY), plant density, tiller density, lodging, and rust (caused by Puccinia spp.) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 30 publications
4
58
0
Order By: Relevance
“…The first phase, funded largely by DOE, has involved evaluation of existing germplasm across much of the historical range of switchgrass in the USA. Multi-location cultivar evaluations have helped to define adaptation zones of existing cultivars, identifying the importance of photoperiod, cold tolerance, and heat tolerance in limiting the breadth of adaptation of most switchgrass cultivars Casler et al 2004;Cassida et al 2005a, b;Fike et al 2006a, b). These studies have also illustrated the remarkably broad adaptation range of cultivars such as Cave-in-Rock, which has superior biomass production far north and east of its origin (Madakadze et al 1998;Casler and Boe 2003) but reduced performance in northern dryland environments (Jefferson et al 2002;Berdahl et al 2005).…”
Section: St Century Transition In Switchgrass Feedstock Research: Dmentioning
confidence: 99%
“…The first phase, funded largely by DOE, has involved evaluation of existing germplasm across much of the historical range of switchgrass in the USA. Multi-location cultivar evaluations have helped to define adaptation zones of existing cultivars, identifying the importance of photoperiod, cold tolerance, and heat tolerance in limiting the breadth of adaptation of most switchgrass cultivars Casler et al 2004;Cassida et al 2005a, b;Fike et al 2006a, b). These studies have also illustrated the remarkably broad adaptation range of cultivars such as Cave-in-Rock, which has superior biomass production far north and east of its origin (Madakadze et al 1998;Casler and Boe 2003) but reduced performance in northern dryland environments (Jefferson et al 2002;Berdahl et al 2005).…”
Section: St Century Transition In Switchgrass Feedstock Research: Dmentioning
confidence: 99%
“…Similarly, yield and winter survival declines at high latitude sites, more so for strains of more southern origin, whether of lowland (Casler et al 2004) or upland morphology (Berdahl et al 2005). Responses to precipitation are ambiguous; some research has found that yields were not strongly correlated with precipitation inputs (Cassida et al 2005b), whereas many investigators have found positive correlations between precipitation and yield, with sensitivity to soil moisture differing between ecotypes (Berdahl et al 2005, Cassida et al 2005b, Lee and Boe 2005, Fike et al 2006a. The high degree of phenotypic and ecotypic variation is not surprising, given the cytotypic diversity within switchgrass.…”
Section: Switchgrassmentioning
confidence: 99%
“…Management factors play a role as well; low rainfall in August-September reduced yields in a two-cut, but not in a one-cut system (Reynolds et al 2000). Soil texture and depth, topography (e.g., distance from a stream), supplemental irrigation, different cultivar requirements, or excess rainfall close to harvest could all confound an overall relationship between yield and annual or "growing season" precipitation (Cassida et al 2005b). Very high growing season precipitation could also correlate with extensive cloud cover and associated low levels of solar radiation, tending to reduce yield.…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation of switchgrass in this region will require cultivars adapted to northern latitudes. Northern ecotypes have a longer winter dormant period with better winter survival than southern ecotypes when grown at the same latitude [3]. The attributes of switchgrass for a biomass crop include its yield potential, longevity, water use and nutrient use efficiency, and suitability for marginal land.…”
Section: Introductionmentioning
confidence: 99%